Joshua, Moses and the land Tetrateuch-Pentateuch-Hexateuch in a generation since 1938 - Auld, A. Graeme (Edinburgh, Scotland T and T Clark, 1980)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Joshua -- criticism, interpretation, etc